TEKNIK PEMBUATAN ANTI VIRUS DENGAN METODE PENCARIAN HEADER FILE DATA SIZEOFCODE DAN ADDRESSOFENTRYPOINT SEBAGAI PATTERN VIRUS - Aah Sumiah; Dian Mardiayansyah (NUANSA INFORMATIKA, 2011)
The rapid advances in information technology especially in the field of computer and network technology, and security issues are often discussed. Starting from the immediate threat crackers or malicious hackers to infect through a program called malcode (malicious code). A program or script that is destructive or harmful to categorize as malcode includes computer viruses, worms or Trojan horses.Developments in Indonesia spread malcode initially more dominated by worms and viruses that come from abroad. But in October 2005, this dominance began to crumble with the spread of local viruses in every computer in Indonesia, the virus spreads very quickly and is very uncomfortable for the user to make a computer, so they invented anti-virus as a solution to prevent the spread.Anti Virus Search Method with Data File Header Sizeofcode and Addressofentrypoint is as Virus Pattern-based observations even though the virus writer has to do a custom header dos in order to reduce the size of the virus, but the data header optimal form of the virus and AddressOfEntryPoint SizeOfCode, will not changeKeyword : Anti Virus, Header File, Sizeofcode, AddressOfEntryPoint, Patern Virus, Delphi